2022
DOI: 10.3390/ijms23073453
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of YY1 in HPV Life Cycle and Cervical Cancer Development

Abstract: Human papillomaviruses (HPVs) are considered to be key etiological agents responsible for the induction and development of cervical cancer. However, it has been suggested that HPV infection alone may not be sufficient to promote cervical carcinogenesis, and other unknown factors might be required to establish the disease. One of the suggested proteins whose deregulation has been linked with oncogenesis is transcription factor Yin Yang 1 (YY1). YY1 is a multifunctional protein that is involved not only in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 136 publications
0
9
0
Order By: Relevance
“…Transcription factor yin yang 1 (YY1) can bind to gene promoters in a variety of cells, regulating downstream transcription and thereby affecting protein expression (12). Numerous reports (13)(14)(15) have demonstrated that YY1 is significantly upregulated in a variety of types of cancer, including breast cancer, lung cancer and glioma. YY1 can play a role in regulating cell proliferation, epithelial to mesenchymal transition and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor yin yang 1 (YY1) can bind to gene promoters in a variety of cells, regulating downstream transcription and thereby affecting protein expression (12). Numerous reports (13)(14)(15) have demonstrated that YY1 is significantly upregulated in a variety of types of cancer, including breast cancer, lung cancer and glioma. YY1 can play a role in regulating cell proliferation, epithelial to mesenchymal transition and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…YY1 is involved in inflammation and tumorigenesis [ 26 , 46 ]. In particular, YY1 is known to be involved in viral diseases, playing a role in the activation of HIV-1 replication [ 47 ] and in the promotion of oncogenic HPV [ 48 ]. AP-1 modulates proliferation, differentiation, apoptosis, and inflammation [ 49 ] and has a central role in the induction of IL-1β production and secretion mediated by nuclear translocation of activated AP-1 [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular transcription factors including Ying-yang 1(YY1), Nuclear-factor 1(NF1), Activator protein 1 (AP1), Glucocorticoid receptor (GR) and Progesterone receptor (PR), among others, can bind to the cognate site in this region for viral gene expression regulation. Additionally, viral E2 protein binding to cognate sites inside the LCR stimulate or to suppress the viral transcriptional activity with effects depending on different HPV types and variants [ 19 , 20 , 21 ]. The E region encodes all the non-structural E1, E2, E4, E5, E6 and E7 proteins, with them having major functions in viral replication and cell transformation [ 22 ].…”
Section: Human Papillomavirus: Classification Structure and Replicati...mentioning
confidence: 99%